Effect of pH and enzyme loading on the protein concentration during collocalia fuciphaga hydrolysis - Ahmad Afifi, Ibrahim (2013)
The purpose of this study is to investigate the effect of pH and enzyme loading on the concentration of protein during enzymatic hydrolysis of Collocalia Fuciphaga.C. Fuciphaga is refers to the bird nest from one swiftlet species that is used as the sample known to be highly nutritious.Bovine Serum Albumin(BSA),a standard protein solution was used as the benchmark for the reference of the protein concentration.A research had been proposed in this study to optimize the production of protein from C.Fuciphaga. The effect of changing of the parameters values during the enzymatic hydrolysis was studied and the higher protein concentrations produced were highlighted.The standard protein curve of Bovine Serum Albumin(BSA)is prepared first with several dilutions for protein standard curve.The results from two significant parameters in the experiment was taken and analyzed.The selection of parameters values was taken from the enzymes’optimum condition where the pH value of Alcalase 2.4L is from pH 7 until pH 10 whiles the temperature is fixed at 50oC.Enzyme loading was varies from 1.5% to 3.0% (v/w).The sample was analyzed using UV-Vis Spectrophotometer to determine the concentration of protein in each sample.The optimum condition is found to be at extraction condition of pH 8.5 and enzyme concentration of 3.0% (v/w).Characterization of the sample had been done and validated the protein composition on the extracted sample.